2018
DOI: 10.3390/ijerph15122902
|View full text |Cite
|
Sign up to set email alerts
|

IQOSTM vs. e-Cigarette vs. Tobacco Cigarette: A Direct Comparison of Short-Term Effects after Overnight-Abstinence

Abstract: Introduction: Research from Philip Morris International’s science division on its Heat-not-Burn product IQOSTM focused on its chemical, toxicological, clinical, and behavioral aspects. Independent research on the experiences and behavioral aspects of using IQOSTM, and how it compares to e-cigarettes, is largely lacking. The current randomized, cross-over behavioral trial tried to bridge the latter gaps. Methods: Participants (n = 30) came to the lab on three consecutive days after being overnight smoking absti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 57 publications
0
45
0
1
Order By: Relevance
“…Accordingly, it is paramount to expand the evidence concerning these products, with details worth being sought ranging from cardiovascular effects to additivity and polluting impact. Indeed, while the dramatic and persisting indoor polluting effect of TCC is very clear, MRP also adversely modify indoor ambient air [ 20 ], for instance, by releasing PM and other established or potentially toxic agents [ 35 ]. This holds true for HNBC as well as EVC, despite their evident inherent differences [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, it is paramount to expand the evidence concerning these products, with details worth being sought ranging from cardiovascular effects to additivity and polluting impact. Indeed, while the dramatic and persisting indoor polluting effect of TCC is very clear, MRP also adversely modify indoor ambient air [ 20 ], for instance, by releasing PM and other established or potentially toxic agents [ 35 ]. This holds true for HNBC as well as EVC, despite their evident inherent differences [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might hold even truer when specific flavors are used, given the potential to increase exponentially the release of potentially hazardous agents, putting particularly some individuals at risk who could be more susceptible than others [ 17 ]. Accordingly, several reports have highlighted that MRP cannot be considered risk-free, given the multidimensional hazards associated with their use, chronic as well as acute [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Active intervention, e.g., with standardized smoking cessation programs, kept patients from smoking for longer times [57]. Offering of alternative products, e.g., e-cigarettes or tobacco heat systems, were helpful in reducing acute cravings for cigarettes [58]. However, the effects of this kind of intervention on the clinical outcome of orthopedic/trauma surgery have yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A study published in 2018 has showed that short-term use of a specific HnB product, IQOS, may be effective to momentarily reduce acute cigarette craving while having a minimal impact on the eCO (abbrev. exhaled carbon monoxide) levels [28]. Another study from 2017 has concentrated on the hazards and toxicity of iQOS.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%